Investigation on aflatoxin M1 content of traditional cheese wagashi produced in Benin - SESSOU, PHILIPPE; FAROUGOU, SOUAÏBOU; YEHOUENOU, BONIFACE B.; AGBANGNAN, P.; AZOKPOTA, PAULIN; YOUSSAO ABDOU KARIM, ISSAKA; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2013)
Mould growth on food is a common and recurring problem often leading to occurrence of mycotoxins inside foodstuffs. Mycotoxins are toxic metabolites known to induce serious health threats such as liver, kidney or nervous system damage, immunosuppression and carcinogenesis in animals and human. Aflatoxin M1 (AFM1) particularly is a carcinogenic metabolite often found in dairy products especially cheese. The aim of this study was to determine the presence of AFM1 in traditional cheese wagashi produced in Benin in order to evaluate possible hazards for consumers of this by-product largely appreciated and consumed by the populations in replacement of eggs and meat. It had consisted to collect fifty samples of wagashi near its retailers from seven markets in Benin and to analyze these samples for the detection of AFM1 by thin layer chromatography using aflatoxin M1 and Griseofulvin standards. Results obtained from this study showed that all samples analyzed were free of AFM1. However, all these samples contained other secondary metabolites which were not identified due to lack of references data and standards. Although samples analyzed were free of AFM1, the presence of other metabolites in cheese wagashi may pose serious health threats for consumers
Keywords: investigation; aflatoxin; cheese wagashi; Benin